THE FUNDS STATEMENT AS AN ANALYSIS TOOL. - Stone, Williard E. (The Accounting Review, 1959)
Abstract This article focuses on the funds statement as an analysis tool. Basically the funds statement presents the story of what happened to the funds provided by net income. For a small business an analysis of net income disposition is often helpful to prove to the owner that the profit on which the income tax is computed has actually been earned. To the small business man it is best, perhaps, to make this profit disposition explanation in terms of cash. In the case of a large corporation, however, the balance sheet contains many varied current assets and current liabilities. The funds statement discloses in a single figure the year's net increase or decrease in liquidity position. By further analysis this change can be appraised and related to other items of the statement. The amount declared as dividends, preferred and common, is clearly set forth in the funds statement. More important than the absolute amount of such dividends, however, is their relative significance. In the fund-change statement, as in no other accounting report, there is presented the story of depreciation and its real significance to the business.